2018
DOI: 10.3174/ajnr.a5540
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy in Wake-Up Stroke and Stroke with Unknown Symptom Onset

Abstract: Mechanical thrombectomy in selected patients with wake-up stroke allows a good functional outcome comparable with that of controls. Outcome after mechanical thrombectomy in daytime-unwitnessed stroke seems to be inferior compared with that in controls. Advanced imaging modalities may increase the frequency of good functional outcome in both patients with wake-up stroke and daytime-unwitnessed stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
2
7
2
1
Order By: Relevance
“…In line with Guo et al [6] and Zhang et al [18], there appears to be no increased risk for ICH in patients with severe LA undergoing MT. In the present study, wake-up stroke was associated with ICH but not with sICH [30].…”
Section: Discussioncontrasting
confidence: 51%
“…In line with Guo et al [6] and Zhang et al [18], there appears to be no increased risk for ICH in patients with severe LA undergoing MT. In the present study, wake-up stroke was associated with ICH but not with sICH [30].…”
Section: Discussioncontrasting
confidence: 51%
“…Thus, the comparability of these results to our data is limited. In contrast, Bücke et al showed that patients with daytime unwitnessed stroke, which included an unspecified proportion of LKWu patients, have a worse outcome 3 months after ET than patients with a known onset [12]; however, the multivariable analyses were not adjusted for the ASPECT score that we identified as key predictor, which may explain the difference to our results. Tortuyaux et al observed a comparable outcome of patients with unknown onset at 3 months, including 34% of LKWu patients, compared to controls with known onset after adjustment for confounders [13]; however, only a subset of patients in that study had LVOS and underwent ET, limiting comparability to our data.…”
Section: Discussioncontrasting
confidence: 92%
“…Similar observations have been reported, where time to treatment did not affect the functional outcome at 3 months. [ 17 ] Our results reaffirm the fact that when selected based on tissue characteristics, delayed window patients perform as well as those presenting early in real world setting.…”
Section: Discussionsupporting
confidence: 79%